Techno-economic analysis of solar greenhouses - Benli, Hüseyin (Taylor and Francis Inc., 2020)
Greenhouses are used in agriculture to control climate allowing crops to be grown year-round. To evaluate greenhouse efficacy, the monthly heat requirement was determined using two types of 1-dimensional dynamic calculation models in two types of greenhouses at six locations. Climate parameters and geographical conditions of locations were determined. The cost of a gable-roofed double polyethylene (PE) greenhouse was 10% greater than an arc-roofed double PE greenhouse of the same size. The models demonstrated good agreement indicating use of either was valid. The arc-roofed type greenhouse had more heat loss than the gable-roofed greenhouse of the same size and decisions on type of greenhouse to use will have to be made based on a cost: benefit analysis of the greenhouse types and the crops grown. © 2019, © 2019 Taylor & Francis Group, LLC.
Keywords: Climate analysis; Eastern Anatolia Region; heating; Turkey